1999
DOI: 10.1046/j.1365-2605.1999.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic treatment of spermatozoa with a trypsin solution, SpermSolute: improved motility and enhanced ATP concentration

Abstract: We have developed a solution, fully described in this report, that can be used in a pretreatment procedure to promote liquefaction and to enhance motility during preparation of spermatozoa. It was applied to native ejaculates prior to swim-up and, in parallel investigations, motility and adenosine triphosphate concentration were compared in treated and untreated samples, which revealed that the solution significantly improved both parameters. The solution, named SpermSolute, is based on a proteinase (trypsin),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Several other enzymes like α-chymotrypsin, lysozyme or hyaluronidase have also been described for this purpose. Recently, a special trypsin-based dissolving solution, SpermSolute, has been reported [297]. However, as these enzymes can also damage spermatozoa, special care should be taken to remove the enzymes by washing procedures as soon as liquefaction is completed.…”
Section: In Vitro Treatment Of Spermatozoamentioning
confidence: 99%
“…Several other enzymes like α-chymotrypsin, lysozyme or hyaluronidase have also been described for this purpose. Recently, a special trypsin-based dissolving solution, SpermSolute, has been reported [297]. However, as these enzymes can also damage spermatozoa, special care should be taken to remove the enzymes by washing procedures as soon as liquefaction is completed.…”
Section: In Vitro Treatment Of Spermatozoamentioning
confidence: 99%
“…, 1994; Lanzafame et al. , 1994; Minhas & Ripps, 1996; Figenschau & Bertheussen, 1999; Terriou et al. , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Loskutoff et al (2005) reported that DGC of semen with trypsin added to density layers had no detrimental effects on sperm motility or viability [14]. Furthermore, trypsin treatment of human sperm, prior to swim up, resulted in increased motility and adenosine triphosphate (ATP) concentration [37]. Westhoff and Kamp (1997) suggested that the increased ATP concentration could be attributed to the activation of the glycolytic enzyme glyceraldehyde triphosphate dehydrogenase (GADPH) by trypsin [38], explaining the improved motility.…”
Section: Discussionmentioning
confidence: 99%